O01.2 Genetic, structural, and surface antigenic variation of treponema pallidum's OMPeome: steps towards a global syphilis vaccine. (14th July 2019) - Hawley, Kelly; Luthra, Amit; Vake, Carson La; Ledoyt, Morgan; Chen, Wentao; Heping, Zheng; Yang, Bin; Juliano, Jonathan J; Parr, Jonathan B; Radolf, Justin; Salazar, Juan; Camaino, Melissa
Abstract : Background: The failure of current prevention strategies to curtail the spread of syphilis, including mother-to-child transmission, underscores the need for a vaccine with worldwide efficacy. Characterization of variation within T. pallidum ( TPA ) outer membrane proteins (OMPs) is critical for this goal. Methods: ClustalW identified polymorphisms within 21 β-barrel forming OMPs ( TPA 's OMPeome) of 15 unique TPA strains. Structural models and conformational B-cell epitopes (BCEs) were predicted. Clade assignments were made using tp0548 and tp0558 sequences. Results: TPA OMPeomes contain four paralogous families (Tpr, FadL, OmpW, and efflux pump OMPs) and orthologs for BamA and LptD. The Tprs group into Subfamilies I (C/D/I), II (E/G/J) and III (B/H/L); Tpr β-barrel domains contain 10 β-strands and five extracellular loops (ECLs) harboring BCEs. TprI is invariant, while TprC and TprD have variability located predominantly in ECLs. The closely related TprE and TprJ β-barrels exhibit extremely low variability. TprG β-barrels variants contain a 23 aa insertion derived from TprE or TprJ. The TprB and TprH β-barrels are fully conserved; there are two TprL β-barrels variants. The FadL orthologs (TP0548, TP0856, TP0858, TP0859, TP0865) consist of 14-stranded β-barrels with seven ECLs harboring predicted BCEs. Variability among FadLs range between fully conserved (TP0856) to highly variable (TP0548). Both OmpWs are fully conserved and consist of 8-stranded β-barrels with four ECLs containing BCEs. The highly conserved efflux pump OMPs (OprJ/TP0966, OprN/TP0967, TolC/TP0969) likely form homotrimeric 12-stranded β-barrels. The 18-stranded BamA/TP0326 β-barrel contains a single aa substitution in ECL4. The LptD/TP0515 β-barrel contains 24 β-strands, 12 ECLs and numerous BCEs, which cluster primarily into two variants. Most OMPs do not align with clade designations. Conclusion: 1.) TPA OMPs display variable degrees of sequence and surface antigenic variation. 2.) TPA OMPeomes are mosaics likely resulting from recombination among circulating strains. 3.) Our analysis enables selection of variable and non-variable OMPs for assessment of protective capacity. Disclosure: No significant relationships.